Growing up tobacco free : preventing nicotine addiction in children and youths - Lynch, Barbara S.; Bonnie, Richard J.; Institute of Medicine (U.S.). Committee on Preventing Nicotine Addiction in Children and Youths (Washington, D.C. : National Academy Press, 1994)
A report from the Committee on Preventing Nicotine Addiction in Children and Youths, Division of Behavioral Sciences and Mental Disorders, the Institute of Medicine.
Toward a youth-centered prevention policy -- The nature of nicotine addiction -- Social norms and the acceptability of tobacco use -- Tobacco advertising and promotion -- Prevention and cessation of tobacco use -- Tobacco taxation in the United States -- Youth access to tobacco products -- Regulation of the labeling, packaging, and contents of tobacco products -- Coordination of policies and research.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Children -- Tobacco use -- United States -- Prevention; Youth -- Tobacco use -- United States -- Prevention; Children; Infants; Smoking Prevention; Adolescent; Child; Infant; Smoking; Tobacco Use Disorder; Tobacco Use Disorder -- prevention & control; United States; Enfants -- Tabagisme -- États-Unis -- Prévention.; Jeunesse -- Tabagisme -- États-Unis -- Prévention.; Enfants; Nourrissons; Tabagisme; Enfance; children (people by age group); infants; childhood; SELF-HELP -- Substance Abuse & Addictions -- General; PSYCHOLOGY -- Psychopathology -- Addiction; Infants; Children; Children -- Tobacco use -- Prevention; Youth -- Tobacco use -- Prevention; United States; Tabagisme -- Prévention.; Jeunesse -- Usage du tabac -- Prévention.; Government publications